Clinic management system :electronic medical records systems - Nur Syatirah, Mohd Adzhar (2005)
An Electronic Medical Records system (EMR) is a computerized system designed for user to manage the records of the patients in systematic ways and to make the user easy to records the patient information. This Electronic Medical Records system (EMR) has been applied with the indexing technique based on the Rule-based conditions.A research and analysis on the current system and indexing technique was done to get the better understanding of the system.The Rapid Application Development (RAD) methodology was used in this project development implements iterative development which is used in the system that always changes from time to time. Testing is done every phase of development life cycle to make sure that the system working properly. This project was developed using Macromedia Dreamweaver and Oracle 9i as a database platform. As a final result,this system was fulfilling all the research objectives. This research was successfully developed the Electronic Medical Records system (EMR) prototype system, computerized and optimized the current system using indexing technique based on the rule-based conditions.